A randomized phase I study of the safety and immunogenicity of three ascending dose levels of a 3-antigen Staphylococcus aureus vaccine (SA3Ag) in healthy adults. Issue 15 (8th April 2015) - Nissen, Michael; Marshall, Helen; Richmond, Peter; Shakib, Sepehr; Jiang, Qin; Cooper, David; Rill, Denise; Baber, James; Eiden, Joseph; Gruber, William; Jansen, Kathrin U.; Emini, Emilio A.; et al.
Abstract Background Staphylococcus aureus is a common cause of healthcare-acquired morbidity and mortality and increased healthcare resource utilization. A prophylactic vaccine is being developed that may reduce this disease burden. Methods Volunteers in good general health aged 50–85 (n = 312) and 18–24 (n = 96) years were randomized to receive a single intramuscular dose of one of three dose levels of a non-adjuvanted, 3-antigen S. aureus vaccine (SA3Ag) or placebo. SA3Ag antigens included capsular polysaccharides 5 and 8 (CP5 and CP8), each conjugated to cross-reactive material 197 (CRM197), and recombinant clumping factor A (ClfA). Safety, tolerability, and immunogenicity were evaluated. Results At day 29 post-vaccination, robust immune responses were observed in both age cohorts at all three SA3Ag dose levels. In the primary analysis population, the 50- to 85-year age stratum, geometric mean-fold-rises in competitive Luminex® immunoassay antibody titers from baseline ranged from 29.2 to 83.7 (CP5), 14.1 to 31.0 (CP8), and 37.1 to 42.9 (ClfA), all (P < 0.001) exceeding the pre-defined two-fold rise criteria. Similar rises in opsonophagocytic activity assay titers demonstrated functionality of the immune response. Most injection-site reactions were mild in severity and there were no substantial differences (SA3Ag vs. placebo) with regard to systemic or adverse events. Conclusions In this study of healthy adults aged 50–85 and 18–24 years, SA3Ag elicited a rapid and robust immune response and was well tolerated, with no notable safety concerns.